Effect of Using Hearing Protection and Earphone on Noise Induced Hearing Loss and Tinnitus in Workshop's Workers - Putri Berliana Syah (JURNAL KESEHATAN LINGKUNGAN, 2017)
Noise exposure can leads to health effect such as Noise Induced Hearing Loss (NIHL) and tinnitus. Besides workplace, noise can be obtained from using earphones. The aim of this study was to analyze the effect of using hearing protection and earphone on NIHL and tinnitus in workers at PT DPS machine workshop. This was a cross sectional with observational analytic study design. This study was conducted in 37 workers at PT DPS machine workshop exposed to noise by using simple random sampling. Results showed that noise level in workplace was 88,57 dBA (8 hours TWA) which exceed TLV 85 dBA. Prevalence of NIHL and tinnitus in workplace was respectively 21.6% and 54%. NIHL affected by using hearing protection and earphone (MLR, p < 0.01; p < 0.05 respectively) and tinnitus affected by using earphone (MLR, p < 0.01) after controlled by working period. It can be concluded that prevalence of NIHL and tinitus are relatively high, NIHL affected by using hearing protection and earphone while tinnitus affected by using earphone. It is recommended for workers to use hearing protection in noise workplace and to reduce using earphone while PT DPS must provide hearing protection and do brieï¬ ng to increase workers' awareness about using hearing protection.